1995
DOI: 10.1161/01.hyp.25.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Increases Vascular Permeability Factor Gene Expression by Human Vascular Smooth Muscle Cells

Abstract: Angiotensin II (Ang II) has been implicated in the pathogenesis of the vascular injury associated with hypertension and diabetes mellitus. Increased vascular permeability is an important early manifestation of endothelial dysfunction and the pathogenesis of atherosclerosis. How Ang II contributes to endothelial dysfunction and promotes an increase in vascular permeability is unknown but is classically attributed to its pressor actions. We demonstrate that human vascular smooth muscle cells express abundant mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
153
1
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(165 citation statements)
references
References 27 publications
7
153
1
4
Order By: Relevance
“…These include not only glucose [37] but also advanced glycation end products (AGEs) [38] and protein kinase-C activation [39,40]. Of particular relevance to our study, angiotensin II also stimulates VEGF expression, an action mediated by the AT1 receptor as indicated by the attenuation of this effect by the AT1 receptor antagonist, losartan [13,41]. Furthermore, in addition to its effects of on VEGF expression, angiotensin II also increases expression of VEGF Receptor-2 (VEGFR-2) [42] thereby potentially increasing tissue responses to VEGF.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These include not only glucose [37] but also advanced glycation end products (AGEs) [38] and protein kinase-C activation [39,40]. Of particular relevance to our study, angiotensin II also stimulates VEGF expression, an action mediated by the AT1 receptor as indicated by the attenuation of this effect by the AT1 receptor antagonist, losartan [13,41]. Furthermore, in addition to its effects of on VEGF expression, angiotensin II also increases expression of VEGF Receptor-2 (VEGFR-2) [42] thereby potentially increasing tissue responses to VEGF.…”
Section: Discussionmentioning
confidence: 88%
“…In vitro studies have shown that angiotensin II (AII) directly stimulates the secretion of VEGF in cultured vascular smooth muscle [12] and in cardiac endothelial cells [13]. Whether this relation between the RAS and VEGF secretion applies to the in vivo setting has not, however, been examined.…”
mentioning
confidence: 99%
“…These results describe a new action of angiotensin II on podocytes, notably the induction of VEGF expression. The potent activity of VEGF suggests a novel mech- anism whereby angiotensin II could locally and directly influence the vascular permeability independent of changes in hemodynamics (Williams et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…ACE inhibitors attenuate the formation of angiotensin II and the break-down of bradykinin. Studies in vitro have shown that angiotensin II is able to stimulate the expression of VEGF in bovine retinal pericytes [20], rat heart endothelial cells [26], as well as human vascular smooth muscle [10,16,17] and mesangial cells [18,19]. Moreover, increased concentrations of angiotensin II have been found in the vitreous fluid of patients with proliferative diabetic retinopathy [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic children with increased plasma concentrations of prorenin are at a high risk for the development of retinopathy [15]. In vitro studies indicate that angiotensin II stimulates the secretion of VEGF by vascular smooth muscle cells [10,16,17], mesangial cells [18,19] and pericytes [20]. The induction of VEGF by angiotensin II requires hyperglycaemic [16] or oxidative conditions [17], which are states that accompany diabetes.…”
mentioning
confidence: 99%